2016
DOI: 10.1097/mib.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Motility in Unaffected Small Bowel is Linked to Inflammatory Burden and Patient Symptoms in Crohnʼs Disease

Abstract: Objectives: Inflammation related enteric dysmotility has been postulated as a cause for abdominal symptoms in Crohn's disease (CD). We investigated the relationship between MRI-quantified small bowel (SB) motility, inflammatory activity and patient symptom burden.Methods: The Harvey Bradshaw Index (HBI) and fecal calprotectin were prospectively measured in 53 CD patients (median age 35, range 18-78) the day before MRI enterography which included a dynamic (cine), breath-hold motility sequence, repeated to enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…Previously, using a single-centre study design in 53 Crohn's subjects, Menys et al 15 reported a significant inverse correlation between motility variance and HBI (r = -0.45, p < 0.001). There was also a significant inverse correlation between motility variance and the HBI symptom components of well-being, abdominal pain and number of liquid stools (r = −0.4, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, using a single-centre study design in 53 Crohn's subjects, Menys et al 15 reported a significant inverse correlation between motility variance and HBI (r = -0.45, p < 0.001). There was also a significant inverse correlation between motility variance and the HBI symptom components of well-being, abdominal pain and number of liquid stools (r = −0.4, p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…15 The observers had access to both cine motility loops and anatomical small bowel images to aid ROI placement. Specifically, small bowel demonstrating the typical stigmata of CD (such as wall thickening, abnormal T 2 signal hyper enhancement etc.)…”
Section: Motility Assessmentmentioning
confidence: 99%
See 3 more Smart Citations